PA 08-4-2305 School children practices as pedestrians in karachi, pakistan. (November 2018) - Khan, Uzma Rahim; Zia, Nukhba; Naeem, Rubaba
Abstract : Pedestrian road traffic crashes are responsible for a substantial number of injuries and deaths in Pakistan. There is a need to better understand the situations faced by pedestrians especially children. The objective of this study was to develop and pilot observation tool for pedestrian's behavior and road practices of school children in Karachi. The survey was conducted from March to June 2013. Initially 175 schools were approached out of which (n=107, 61.1%) agreed to participate. The observations were made on school children as pedestrians (coming to and going from school) by trained data collectors. The observations were made during morning (starting time of school) and afternoon (off time of school). Three hundred and forty-four pedestrian observations were made in 107 schools. Of the 107 schools, 50.47% were private (n=54), 44.86% were public (n=48), and the rest were non-governmental organization run (n=5, 4.67%) schools. Most of the schools (n=227, 66.6%) lacked a zebra crossing. None of the observed children used zebra crossing, when present. Only a quarter of the children looked right and left while crossing the road (n=85, 24.7%). Almost one third of the children had their back towards oncoming traffic while walking on road (n=109, 31.7%). About 10.5% (n=36) children ran to cross the road. About 36.3% (n=125) children did not look out for traffic before stepping on to the road. This was the first time that safety behaviors of children in school as pedestrians were measured in Pakistan. There is need for improved safety for child pedestrians while promoting the health and environmental benefits of walking.